2011
DOI: 10.1007/s12588-011-9016-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of pectin/gelatin hydrogel membranes for wound dressing

Abstract: The present work deals with the development of pectin-gelatin (PEGE) hydrogel membranes for wound dressing applications. The prepared hydrogels were characterized by FTIR spectroscopy, XRD spectroscopy, water vapor transmission rate (WVTR) test and tensile strength test. Morphology and thermal stability of the membranes were analyzed by Field emission scanning electron microscopy (FESEM) and thermogravimetric analysis (TGA). The swelling studies of the hydrogels were conducted in different pH buffer solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(69 citation statements)
references
References 39 publications
2
66
0
1
Order By: Relevance
“…Studies on the thermal properties of gelatin showed that it exhibits three main thermal degradation steps, the first being attributed to water desorption, and the others associated with protein degradation [25,26]. Gelatin thermal degradation kinetics has an activation energy ( ) ranging between 175 and 275 kJ.mol -1 , the values increasing with the protein's molecular weight [25,27].…”
mentioning
confidence: 99%
“…Studies on the thermal properties of gelatin showed that it exhibits three main thermal degradation steps, the first being attributed to water desorption, and the others associated with protein degradation [25,26]. Gelatin thermal degradation kinetics has an activation energy ( ) ranging between 175 and 275 kJ.mol -1 , the values increasing with the protein's molecular weight [25,27].…”
mentioning
confidence: 99%
“…The water vapor transmission rate (WVTR) test was carried out using the method adapted from the previous study 20 . Briefly, films with dimension of 30 mm x 30 mm was cut and put as a cap of a glass vial with a diameter 16 mm containing 10 mL distilled water, followed by the system being weighed and recorded.…”
Section: Water Vapor Transmission Ratementioning
confidence: 99%
“…An ideal wound dressing should control the water loss from a wound at an optimal rate (Mishra et al, 2011). The water vapor permeability of a wound dressing should prevent excessive dehydration as well as the build-up of exudates (Balakrishnan et al, 2005).…”
Section: Permeability and Swelling Testsmentioning
confidence: 99%